Intraoperative monitoring of lower cranial nerves in skull base surgery: technical report and review of 123 monitored cases - Topsakal, Cahide; Al-Mefty, Ossama; Bulsara, Ketan R.; Williford, Veronica S. (Springer, 2008)
The fundamental goal of skull base surgery is tumor removal with preservation of neurological function. Injury to the lower cranial nerves (LCN; CN 9-12) profoundly affects a patient's quality of life. Although intraoperative cranial nerve monitoring (IOM) is widely practiced for other cranial nerves, literature addressing the LCN is scant. We examined the utility of IOM of the LCN in a large patient series. One hundred twelve patients underwent 123 skull base operations with IOM between January 1994 to December 1999. The vagus nerve (n=37), spinal accessory nerve (n=118), and the hypoglossal nerve (n=83) were monitored intraoperatively. Electromyography (EMG) and compound muscle action potentials (CMAP) were recorded from the relevant muscles after electrical stimulation. This data was evaluated retrospectively. Patients who underwent IOM tended to have larger tumors with more intricate involvement of the lower cranial nerves. Worsening of preoperative lower cranial nerve function was seen in the monitored and unmonitored groups. With the use of IOM in the high risk group, LCN injury was reduced to a rate equivalent to that of the lower risk group (p > 0.05). The immediate feedback obtained with IOM may prevent injury to the LCN due to surgical manipulation. It can also help identify the course of a nerve in patients with severely distorted anatomy. These factors may facilitate gross total tumor resection with cranial nerve preservation. The incidence of high false positive and negative CMAP and the variability in CMAP amplitude and threshold can vary depending on individual and technical factors.
Keywords: skull base surgery; intraoperative monitoring; lower cranial nerves; electromyography; electrophysiological monitoring